2023
DOI: 10.3390/app132111945
|View full text |Cite
|
Sign up to set email alerts
|

Sorbets as Functional Food Products, Unexplored Food Matrices, Their Challenges, and Advancements

Jackson Williams,
Andrew J. McKune,
Nenad Naumovski

Abstract: Functional foods and beverages are becoming one of the leading food products on the global market today. This is predominately due to the consumer, industry and research-related interests in the use of food-derived products for the management of several chronic conditions. The diversity of currently available functional food products also provides an opportunity for the use of fruit-based sorbets as a carrier of functional ingredients. Therefore, the aim of this literature review is to explore the use of sorbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 109 publications
0
2
0
Order By: Relevance
“…Recent studies have shown positive results regarding the growth and survival of probiotics in frozen desserts, especially in relation to the cold shock response due to increases in the ability to adapt to the low temperature of the final product during storage [16,18,19,22,103,112,119].…”
Section: Manufacturing Process and Storage Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have shown positive results regarding the growth and survival of probiotics in frozen desserts, especially in relation to the cold shock response due to increases in the ability to adapt to the low temperature of the final product during storage [16,18,19,22,103,112,119].…”
Section: Manufacturing Process and Storage Conditionsmentioning
confidence: 99%
“…The circumstances of production and preservation of these products need to be surveyed as well [20]. The scientific papers on challenges in the production of probiotic frozen desserts [21] and the issue of probiotic viability in frozen food products [22] are available in the current literature.…”
Section: Introductionmentioning
confidence: 99%